Monitoring Suhu Pada Tanaman Seledri Berbasis Internet of Things Dengan Metode Fuzzy Sugeno - Banggut, Andreas Lois Figo; Setiawan , Aries Boedi; Sumarahinsih , Andrijani (Program Studi Teknik Elektro - Fakultas Teknik - Universitas Widyagama Malang, 2023)
In the process of plant growth is influenced by many factors one of which is the weather climate. Many crop failures occur due to unstable weather. One of them is the celery plant because it is susceptible to weather. Therefore an automatic temperature monitoring system is designed that can be monitored from a smartphone using a fuzzy Sugeno method. Starting from reading the DHT11 sensor which is then processed by ESP32 which then sends the data to the smartphone via the Inventor App, then ESP32 gives commands to the output which then works based on the conditions that occur from the results of sensor readings with PWM fuzzy sugeno. The parameter being monitored is the temperature of the celery plant. The reading results will be displayed on App Inventor as an Internet of Things (IoT) support system